Single species conservation in a multispecies fishery: the case of the Australian eastern gemfish - Pascoe, Sean (Ecological economics, 2000)
The inability of fishers to avoid bycatch when operating in a multispecies fishery can create problems when the bycatch species itself is the subject of conservation-based controls. Increased protection of the bycatch species can only be achieved through a reduction in the overall catch of the fishery. Such a problem has arisen in the Australian south east fishery where the stock of one bycatch species has fallen substantially over recent years. A model of the fishery was used to estimate the costs of protecting the remaining stock and the potential commercial benefits from the recovery of the stock. The analysis suggests that the costs of protecting the stock may be greater than the commercial benefits arising from a recovered stock. Non-market benefits of stock conservation are not included in the model analysis, but are considered in the discussion.